Enantioselective Phosphine‐Catalyzed Formal [4+4] Annulation of α, β‐Unsaturated Imines and Allene Ketones: Construction of Eight‐Membered Rings. Issue 45 (10th October 2017) - Ni, Huanzhen; Tang, Xiaodong; Zheng, Wenrui; Yao, Weijun; Ullah, Nisar; Lu, Yixin
Abstract: The first highly enantioselective phosphine‐catalyzed formal [4+4] annulation has been developed. In the presence of amino‐acid‐derived phosphines, the unprecedented [4+4] annulations between benzofuran/indole‐derived α, β‐unsaturated imines and allene ketones proceeded smoothly, thus affording azocines, bearing either a benzofuran or an indole moiety, in excellent yields and with nearly perfect enantioselectivities (≥98 % ee in most cases). This work marks the first efficient asymmetric construction of optically enriched eight‐membered rings by phosphine catalysis. Abstract : Magic eight "ring" : Under the catalysis of amino‐acid‐derived phosphines, the unprecedented [4+4] annulations between benzofuran/indole‐derived α, β‐unsaturated imines and allene ketones proceeded smoothly to afford azocines in excellent yields and with nearly perfect enantioselectivities. This work marks the first efficient asymmetric construction of optically enriched eight‐membered rings by phosphine catalysis. TBDPS= tert ‐butyldiphenylsilyl, Ts=4‐toluenesulfonyl.